The ground reaction forces in basic stances in shotokan karate as an effective indicator in the prevention of lower limb pain in competitive athletes - Lisowska, A.; Fryzowicz, A.; Maczyñski, J.; Ogurkowska, M. (Archives of Budo, 2021)
Background and Study Aim: Shotokan karate training is based on learning basic stances. Improving the stances in the training process can have a significant impact on the loading of lower limb joints. Given frequent pain symptoms in the area of the knee joints among professional shotokan karate athletes, the aim of this study was knowledge about the magnitude of lower limb dynamic load indicators while performing three basic kata stances. Material and Methods: Participants (n = 15) were male shotokan karate kata athletes (aged 27.5 ±8 years; training experience of 17.5 ±4.8 years). During the study, the ground reaction forces (GRFs) during dynamic transitions were measured. The following functional tests were also performed: Thomas test, Ober test and Patrick test, verifying the occurrence of lower limb muscle contractures. The Foot Posture Index Test was also performed. Results: The GRFs occurring in basic karate stances were statistically significantly different (p<0.05). In the zenkutsu dachi and kokutsu dachi stances their vertical components reached values more than three times higher than the athletes` body weight. All three basic stances (also kiba dachi) showed statistically significant (p<0.05) higher values of the anteroposterior component of GRFs in the group of kata athletes; the occurrence of lower limb muscle contractures, especially hip abductors, was also demonstrated. Conclusions: Due to the impact of the anteroposterior component of GRFs, the kiba dachi is considered to be the most dangerous stance. In order to avoid chronic overload changes of the musculoskeletal system, preventive measures should be implemented for kata athletes. These should focus on minimizing the generated GRFs and preventing muscle contractures.